Rippling waves Aga Mayo Butocan and the transmission of Maguindanao Kulintang music - Liao, Janine Josephine Arianne
This paper explores the journey of the Maguindanaon kulintang music as it is transmitted to non-Maguindanaons by Prof. Aga Mayo Butocan, Maguindanaon kulintang master who taught at the University of the Philippines College of Music.